Two new species of Tingidae (Insecta: Heteroptera) from Papua New Guinea - Guilbert, Eric (Zootaxa, 2021)
Two species of Tingidae (Heteroptera) sampled by fogging at Baiteta, Papua New Guinea, are described as new to science. Comments on their distribution and host-plants as well as an identification key to species of the genera concerned are provided.